Periodontal Diseases Knowledge, Attitudes and Practices of Patients With Hypertension: A Cross-Sectional Study in Two Hospitals in the West Region (Cameroon) - Pascaline Magne Tambe; Sylvain Raoul Simeni Njonnou; Christian Ngongang Ouankou; Christian Deube Ngako; Fernando Kemta Lekpa; Clarisse Mapa-Tassou; Herna Stella Chimy Tchounchui; Siméon Pierre Choukem; Charles Muhima Pilipili (International Journal of Dentistry)
Conclusion: Most participants had insufficient knowledge of oral health and adopted harmful practices. Highlighting the need for carers and decision-makers to raise awareness and educate hypertensive patients about the relationship between their disease and oral health using the associated factors identified.